220k views
4 votes
Explain, step by step , how you solve the system of equations: y=3x - 3,y= x-3. Then provide the solution to the system.

User Archz
by
5.0k points

2 Answers

3 votes

Answer:

x = 0

Explanation:

y=3x-3

y=x-3

They both equal why so you can take away the y and put them equal to each other.

3x-3=x-3

Subtract x from both sides

2x-3=-3

Add 3 to both sides

2x=0

divide 2 from both sides

x=0

The answer is 0. Hope this helps you :)

User Marek Jagielski
by
5.3k points
5 votes

Answer:

(0, -3)

Explanation:

y = 3x - 3

y = x - 3

In the solution to the system of equations, y is the same number for both of those functions. So 3x - 3 = x - 3.

Then solve for x:

3x - 3 = x - 3

Add 3 to both sides

3x = x

Subtract x from both sides

2x = 0

Divide both sides by 2

x = 0

Now that you have x, substitute it in one of the equations:

y = 3x - 3

y = 3(0) - 3

y = -3

x is 0 and y is -3, so the solution to the equation is (0, -3)

User Irini
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.